270 Neonipple Formation After Implantation Of Acellular Ovine Xenograft - Nicholas Andrew Vernice; Sarah Caughey; Nabih Berri; Xue Dong; Jason Harris; Ryan J. Bender; Jason A. Spector (Journal of Clinical and Translational Science, 2022)
OBJECTIVES/GOALS: To determine if decellularized costal cartilage (DCC), which could theoretically be obtained “off the shelf,” would provide similar results to autologous cartilage grafts previously studied in this lab, thereby widening the application of our novel nipple engineering approach to all patients undergoing nipple reconstruction. METHODS/STUDY POPULATION: PLA scaffolds (diameter: 1.0 cm, height: 1.0 cm) were printed using a PRUSA 3D printer and sterilized. Lamb costal cartilage was minced (1 mm3) or zested (<0.2 mm3) and then decellularized. The quality of decellularization was assessed using DNA quantification and histological analysis. DCC was then packed into PLA scaffolds and implanted subcutaneously into immunocompetent Sprague Dawley rats using a CV flap technique. The constructs were explanted and evaluated up to 6 months after implantation. RESULTS/ANTICIPATED RESULTS: All nipple reconstructions showed well-preserved diameter and projection due to persistence of the external scaffolds at 1, 3, and 6 months. Mass and volume of engineered tissue was well-preserved over all timepoints. Compared to implantation values, engineered zested nipples demonstrated a 12% mass increase and a 22% volume increase at 6 months. Minced nipples illustrated a similar mass and volume gain with a 21% increase in mass and a 13% increase in volume at 6 months secondary to infiltration of fibrovascular tissue and growth through scaffold wall pores, respectively. Histologic analysis demonstrated a mild inflammatory infiltrate 1 month after implantation which was replaced by fibrovascular tissue by 3 months that remained stable through 6 months. The processed DCC structure remained unchanged over time. DISCUSSION/SIGNIFICANCE: Using acellular ovine xenograft within bioabsorbable scaffolds, we have engineered neonipples that maintain their volume for at least 6 months. DCC architecture is well-preserved with minimal evidence of immune-mediated degradation. By using DCC, this novel approach to nipple engineering may be applied to any patient requiring reconstruction.